Qatar National Museum-Transit oriented development: the masterplan for the urban regeneration of a "green TOD" - Albandari Al-Harami; Raffaello Furlan (Journal of Urban Management, 2020)
Over the past two decades, a growing number of communities have pursued light rail transit (LRT) and Transit-Oriented Developments (TODs) as part of an integrated transportation and land use strategy to revitalize and/or regenerate the built environment of worldwide cities. In the past few decades, Doha, the capital city of the State of Qatar, has experienced an extraordinary and rapid urban growth, caused by Post-WWII oil and natural gas production, which has transformed the country's economy. As a result, the State of Qatar has invested large funds into the transformation of Doha's built environment and the construction of major urban public transit systems [i.e., the Doha Metro, the Lusail LRT, and a bus rapid transit (BRT)]. This research study explores the urban development of Qatar National Museum's (QNM) Transit Village (TOD) located along Doha Metro's Gold Line, in the proximity of Doha Cornice, the Museum of Islamic Art and MIA Park. The research study aims to propose a masterplan for the urban regeneration of QNM's transit village, based on a Green Urbanism and TOD design strategy.
Keywords: 710; Doha metro; Green urbanism; QNM-TOD; Urban regeneration